Status of Sedentary Time and Physical Activity of Rural Residents: A Cross-Sectional Population-Based Study in Eastern China - Wang, Jiayuan; Wang, Ya; Korivi, Mallikarjuna; Chen, Xi; Zhu, Rong (Frontiers in Public Health, 2022)
Background: The urbanization process may affect the lifestyle of rural residents in China. Limited information exists on the extent of sedentarism and physical activity level of rural residents in middle-income countries. This is the first survey on sedentary time (ST) and physical activity (PA) among rural residents in eastern China. Methods: This cross-sectional observational study randomly sample rural adults from Zhejiang Province in eastern China (n=1320). Participants’ ST and PA levels were determined from the International Physical Activity Questionnaire Short Form through face-to-face interviews, and the influencing factors of PA level were assessed through multi-class logistic regression analysis. Results: The findings showed that the daily ST of the participants ranged from 30 to 660 minutes, with a median of 240 minutes (P25, P75:120-240minutes), and 54.6% of participants were sedentary for 240 minutes or above. The daily ST in men, people aged 18 to 44 years, people with bachelors’ degree and above, people working for government agencies/institutions, people with unmarried status, and people with an average income of <2,000 Yuan was longer than that of other respective groups (p<0.01). In contrast, the daily ST of people with hypertension or with osteoporosis/osteopenia patients was less than that of normal people (p <0.01). Additionally, 69.4% of participants generally had a low level of PA (LPA). Compared with those living in northern Zhejiang, people living in southern Zhejiang who were aged 18-44 years, had bachelor’s degree or above, were farmers, and had household incomes below 10,000 Yuan per month were more likely to engage in LPA compared to people >60 years, with high school/technical education levels or with junior college degrees, working in government agencies and institutions, and with household income above 10,000 Yuan per month (p <0.05). Furthermore, there was no correlation between ST and PA levels. Conclusion: Most rural residents in the Zhejiang Province of eastern China had longer daily ST and a low level of PA. This was predominant in men, young people, highly educated people, unmarried people, and middle to high-income people. Health education programs should be target towards specific population groups to decrease the ST and increase PA.